BILATERAL MOLARIFORM SUPERNUMERARY TEETH IN THE ANTERIOR MAXILLA: A REPORT OF TWO CASES - Mehmet Cem ÖZDEN (Journal of Istanbul University Faculty of Dentistry, 2017)
Supernumerary teeth are additional teeth besides the normal series and can be found in any region of the dental arch. Supernumerary teeth can be classified according to their form and locations. Early diagnosis and treatment of patients with supernumerary teeth may prevent or minimize complications. The treatment options depend on the type and position of the supernumerary tooth and its effect on the adjacent structures. Two male patients were referred to our clinic due to swelling in their maxillae and interrupted eruption of teeth. Upon radiological examination of the patients, impacted supernumerary teeth were found. Surgical removal of these teeth were perfomed and they were found to be molariform. We aim to present the two rare cases of molariform supernumerary teeth in this article.